2020
DOI: 10.1126/sciadv.aba1430
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic interneurons excite neonatal hippocampus in vivo

Abstract: GABAergic interneurons are proposed to be critical for early activity and synapse formation by directly exciting, rather than inhibiting, neurons in developing hippocampus and neocortex. However, the role of GABAergic neurons in the generation of neonatal network activity has not been tested in vivo, and recent studies have challenged the excitatory nature of early GABA. By locally manipulating interneuron activity in unanesthetized neonatal mice, we show that GABAergic neurons are excitatory in CA1 hippocampu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
111
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(125 citation statements)
references
References 53 publications
(81 reference statements)
13
111
1
Order By: Relevance
“…While the above differences related to bumetanide and maturational stage are robust, the relatively high absolute levels of Cl − in these experiments are likely to be attributable to the ongoing activity in the neurons in vivo and to possible technical problems in calibration. Furthermore, the first evidence for functionally excitatory actions of GABAergic interneurons in the immature hippocampus in vivo has recently been published [101]. Similar to the neurons of the immature brain, NKCC1 maintains a high [Cl − ] i in neuronal progenitors of the adult subventricular zone [102,103] and dentate gyrus [104].…”
Section: Functional Data Show CL − Uptake By Nkcc1 In Cns Neuronsmentioning
confidence: 99%
“…While the above differences related to bumetanide and maturational stage are robust, the relatively high absolute levels of Cl − in these experiments are likely to be attributable to the ongoing activity in the neurons in vivo and to possible technical problems in calibration. Furthermore, the first evidence for functionally excitatory actions of GABAergic interneurons in the immature hippocampus in vivo has recently been published [101]. Similar to the neurons of the immature brain, NKCC1 maintains a high [Cl − ] i in neuronal progenitors of the adult subventricular zone [102,103] and dentate gyrus [104].…”
Section: Functional Data Show CL − Uptake By Nkcc1 In Cns Neuronsmentioning
confidence: 99%
“…Using the Cre/loxP system, we conditionally knocked out GAD67 from PV-expressing cerebellar neurons and found that the distribution of the Shaker-type K + channel Kv1.1 was altered, resulting in the abnormal projection of basket cell collaterals onto Purkinje cells, a phenotype that was also observed in GAD65 KO mice. GABA signaling is important for the development of the neural circuits in the cerebral cortex [29] and hippocampus [30,31]. To our knowledge, this is the first report describing the importance of GABA signaling for the development of inhibitory circuits in the cerebellum.…”
Section: Discussionmentioning
confidence: 75%
“…This can indicate a disruption in development of normal and balanced neuronal networks, supporting the increased electrical activity observed in these organoids. It should be noted that several lines of evidence implicate that during development, GABAergic synapses have a depolarizing effect (Obata, Oide and Tanaka, 1978; Ben-Ari et al ., 2007; Murata and Colonnese, 2020). Seizure dynamics in developmental epilepsies are known to be dependent on depolarizing GABA responses, particularly due to an accumulation of intracellular chloride resulting in a depolarized chloride reversal potential, thereby causing increased excitability, instead of hyperpolarization upon activation of GABA A receptors (Khalilov et al ., 2005; Ben-Ari et al ., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence of increased mean spectral power in WWOX-depleted COs and WSM FOs, and its recovery in the presence of lentivirus containing WWOX, further strengthens the idea that depolarizing GABA plays a key role in seizure susceptibility. These findings shed a new light on the lack of efficacy of common anticonvulsant therapies on immature neurons (Khalilov et al ., 2005; Murata and Colonnese, 2020) – making WWOX-depleted COs a useful model to test and study novel therapies targeting excitatory GABAergic responses.…”
Section: Discussionmentioning
confidence: 99%